Emerging Battery Technologies to Boost the Clean Energy Transition Cost, Sustainability, and Performance Analysis - Passerini, Stefano; Barelli, Linda; Baumann, Manuel; Peters, Jens.; Weil, Marcel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This open access book provides a totally new perspective on the rapidly developing sector of electrochemical energy storage, putting a spotlight on its sustainability under consideration of the latest developments and emerging future technologies. A number of selected, high-level authors from different disciplines discuss the potential contribution of batteries to a cleaner society, the need for new battery concepts, necessary new chemistries and their sustainability. These include not only analyses of the most relevant technological developments in the field, but also the latest state of knowledge in terms of their future roles in transport and stationary applications within the clean energy transition, their potential environmental impacts, resource demands and social impacts, and the corresponding methodological advances. All these aspects are analyzed on micro-level (i.e., for the specific technology), but also on macro-scale (i.e., from a systemic perspective), providing a glimpse on how emerging battery systems might cover future energy storage demand. By taking a prospective and interdisciplinary viewpoint, this book will be of interest for a broad field of readers interested in electrochemistry, engineering with particular focus on electric grids, and on-board systems and energy system analysis, but also those worried about the sustainability and societal challenges related with the energy transition(s). Open access, providing free and unlimited access to all interested readers; Covering the entire battery technology value chain, from raw material extraction to manufacturing, use and recycling; Merging circular economy, technology advancements, environment and society into a broad sustainability picture; Linking key aspects for battery development with the imperatives of a clean energy transition and a circular economy.
Introduction -- System perspective for a clean energy transition -- Battery Market perspective -- Overview state of the art batteries, problems, opportunities -- Emerging batteries - closed systems -- Emerging batteries - open systems -- Prospective Assessments of emerging batteries.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Electric batteries; Materials; Chemistry; Renewable energy sources; Batteries; Materials Chemistry; Renewable Energy